A novel data assimilation technique for the plasmasphere. Issue 10 (15th October 2015) - Nikoukar, Romina; Bust, Gary; Murr, David
Abstract: We present a novel technique for imaging and data assimilation of the topside ionosphere and plasmasphere. The methodology is based upon the three‐dimensional variational technique (3DVAR), where an empirical background model is utilized. However, to prevent nonphysical vertical variation in density estimates, we devise statistical methods to enforce a roughness penalty in the traditional 3DVAR optimization. The upward looking total electron content (TEC) observations from the Global Positioning System (GPS) receiver on board Constellation Observing System for Meteorology, Ionosphere and Climate satellites are utilized in the assimilation algorithm. The estimation results show reasonable agreement with in situ density measurements of Defense Meteorological Satellite Program satellites and Van Allen Probes derived densities during geomagnetically quiet and severe storm time conditions, respectively. These preliminary results demonstrate great potential for the use of GPS TEC measurements from low‐Earth orbit satellites in monitoring and studying the morphology and dynamics of large‐scale structures of the electron density in the topside ionosphere and plasmasphere. Key Points: A new plasmasphere data assimilation technique using GPS data is developed Regularization techniques are incorporated in the assimilation algorithm Reasonable agreement is shown with DMSP satellites and Van Allen Probes data